Karakteristik Kualitas Daging Sapi Peranakan Ongole yang Berasal dari Otot Longissimus Dorsi dan Gastrocnemius - Nuraini, Nuraini; Hafid, Harapin (Fakultas Peternakan Universitas Jambi, 2006)
The research target was to know the characteristic of beef quality of Peranakan Ongole cattle with meat sample from Longissimus dorsi and Gastrocnemius. Data of tenderness and characteristic of chemical composition of beef using t-Student test. Result of research indicated that the musculus Longissimus dorsi is more tender than musculus Gastrocnemius. Fat content of musculus Longissimus dorsi was higher than that of musculus Gastrocnemius. On the other hand, water, crude protein and mineral content of musculus Longissimus dorsi was lower than those of musculus Gastrocnemius.